AGE-R3/galectin-3 expression in osteoblast-like cells: Regulation by AGEs - Mercer, Natalia (2004)
The accumulation of irreversible advanced glycation endproducts (AGEs) on long-lived proteins, and the interaction of AGEs with cellular receptors such as AGE-R3/galectin-3 and RAGE, are considered to be key events in the development of longterm complications of diabetes mellitus, Alzheimer’s disease, uremia and ageing. The aim of this study was to investigate the expression and sub-cellular distribution of galectin-3, as well as its possible modulation by AGEs, in MC3T3E1 mouse calvaria-derived osteoblasts and in UMR 106 rat osteosarcoma cells. Both osteoblastic lines were cultured either with control bovine serum albumin (BSA) or with AGEs-BSA for 48 h. Cells were evaluated for galectin-3 expression by fixing and immunofluorescent microscopic analysis; or Western blot analysis of whole cell extracts, sub-cellular fractions and culture media. Both cell lines express 30 kDa (monomeric) galectin-3, although expression was about 15-fold lower in the UMR106 osteosarcoma cells. Dimeric (70 kDa) galectin-3 was additionally observed in the UMR106 cells. Immunofluorescent analysis of galectin-3 distribution showed a diffuse cytoplasmic and strong nuclear pattern in MC3T3E1 osteoblasts, and a patchy cytoplasmic pattern in UMR106 cells. Western blot analysis for both cell lines showed that galectin-3 was mainly found in the cytoplasm and in minor amounts in the microsomal fraction, while considerable amounts were secreted into the culture media. Exposure to 100–200 μg/mL AGEs-BSA increased the cellular content of 30 kDa galectin-3 (20–25% for MC3T3E1 and 35–70% for UMR106 versus control BSA, p < 0.05), and decreased the culture media levels of galectin-3 (10–20% for MC3T3E1 and for UMR106 versus control BSA, p < 0.05). These results confirm the expression of galectin-3 in osteoblastic cells, and suggest different levels and sub-cellular distribution of this protein in transformed versus non-transformed osteoblasts. Osteoblastic exposure to AGEs alters their expression and secretion of galectin-3, which could have significant consequences on osteoblast metabolism and thus on bone turnover.